Phenomenon of Juvenile Delinquency In Purwokerto Village, Patebon District, Kendal Regency, Central Java - Putri Sekar Pengesthi; Sintiya Wati; Ratna Muthia (Universitas Kristen Indonesia Toraja, 2024)
In Purwokerto Village, Patebon District, Kendal Regency, Central Java, the phenomenon of juvenile delinquency has increased rapidly in recent years. This delinquency includes various behaviors that violate social and legal rules, such as fighting, vandalism, drug abuse, and other violations. To determine the components that contribute to juvenile delinquency in the village and its impact on adolescents' social lives. This study uses a qualitative descriptive methodology. As a result of in-depth interviews and observations of participants, it was found that some of the main factors influencing adolescent deviant behavior are changes in family structure, negative peer influence, and lack of supervision and guidance from family and society. The purpose of this study is to provide practical recommendations to stop and handle juvenile delinquency in Purwokerto Village.